SISTEM PENGATUR TRAFFIC LIGHT MENGGUNAKAN GELOMBANG RADIO BERBASIS MIKROKONTROLER - ., Andri (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
There are several ways in the traffic light settings, such as by networking and standalone system. Both systems are actually able to run well, it's just that there are some obstacles. Constraints on the networking system is the development of cable network system is very complicated. Constraints on standalone systems is a matter of setting it up, because if the setting of the traffic light will be changed, then it must come to a traffic light is located. Thus the need for a solution to the traffic light settings without a cable. The system in question is the control of traffic lights using the medium of radio waves. The use of radio waves only as a means of sending a command to change the duration of traffic lights. There are nine orders given sender module and the receiver module to the three conditions of the traffic light system, this command can each be used in accordance with the traffic conditions (conditions of quiet, solid, and normal). The process of sending data on the system is done by the microcontroller Arduino Nano to the sender module, data is sent and processed by a microcontroller receiver. Software used is the Arduino IDE and programming language C / C ++ with a serial connection through the USB port on a laptop / computer.Based on test results, within a range of the sender and receiver system more or less (Â±) 1,65 meter, the given command may encounter an error, this is due to the frequency used the same four receivers, namely 433 MHz. system has several advantages, including a more practical when compared with the use of cables and setting the duration of time at traffic lights easier. Â  Keywords: networking, standalone, Radio Wave, Microcontroller, Traffic Light.